Antineoplastic agents exacerbate periodontal inflammation and aggravate experimental periodontitis - Gusman, David Jonathan Rodrigues [UNESP]; Ervolino, Edilson [UNESP]; Theodoro, Letícia Helena [UNESP]; Garcia, Valdir Gouveia [UNESP]; Nagata, Maria José Hitomi [UNESP]; Alves, Breno Edson Sendão [UNESP]; de Araujo, Nathalia Januario [UNESP]; Matheus, Henrique Rinaldi [UNESP]; de Almeida, Juliano Milanezi [UNESP] (Wiley, 2019)
Aim: This study evaluated the effects of 5-fluorouracil (5-FU) and cisplatin (CIS) in healthy periodontal tissues and in the early stages of experimental periodontitis (EP) in rats. Methods: One hundred and eighty male rats were divided into three groups, which were submitted to the following systemic treatments: physiological saline solution (PSS); CIS and 5FU. Each group was subdivided into two subgroups: without (NEP) and with (EP) induction of EP. Animals were euthanized at 3, 5 and 7 days post-treatment. Histological, histometric (percentage of bone in the furcation [PBF]) and immunohistochemical (for tumour necrosis factor-α, interleukin-1β and receptor activator of nuclear factor-κB ligand) analyses were performed. Data were statistically analysed. Results: CIS-NEP and 5FU-NEP showed more inflammation than PSS-NEP at 3, 5 and 7 days. CIS-EP and 5FU-EP showed more inflammation and lower PBF than PSS-EP at all periods of evaluation. 5FU-EP showed lower PBF than CIS-EP at 5 and 7 days. Conclusion: 5-FU and CIS exacerbated periodontal inflammation and aggravated the progression of EP in its early stages.
Keywords: alveolar bone loss; antineoplastic agents; cisplatin; fluorouracil; periodontal disease; periodontium